The Effect of Index Card Match Strategy toward Grammar Mastery - Iin Widya Lestari; Ainu Zuhriyah; Kurniaka Insyanatun Khassanah (STAI Miftahul Ula Nganjuk, 2018)
The research aimed to know is any differences in students’ condition before and after giving a treatment and to know the effect of Index Card Match in grammar mastery. This research is experimental research. The population was all eighth-grade students in academic year 2018/2019. It consists of 3 classes, VIII A, VIII B, and VIII C. Using purposive sampling technique, VIII A (experimental class) and VIII B (control class) were chosen as the sample with a total number of students were 25 students in every class. The treatment was conducted in an experimental class in 4 times. The instrument consists of 20 multiple-choice item and 10 completion item questions about grammar test. The data that was collected from preliminary test and post-test were processed using SPSS 18. The result of this research showed that the results of the preliminary test and post-test. It shows that students’ score increase. Students’ score at the preliminary test was classified poor. While at post-test, students mostly classified at very good classification. This result leads to the conclusion that students who were taught by using Index Card Match Strategy achieved higher scores than those who were not.